Evaluation of the vision screening programs in school-age children - Erdem, Seyfettin (Indian Journal of Child Health, 2018)
Background: Visual acuity (VA) screening programs, especially during early childhood, are important for the early detection of eye disorders. Objectives: The objective of this study is to evaluate the effectiveness of eye surveys conducted by guide teachers in school-age children. Design: This was a cross-sectional study. Patients and Methods: Detailed eye examinations were conducted by an ophthalmologist in 462 children aged 5–15 years, who were believed to have impair vision according to the snellen eye chart by guide teachers working in various primary schools between September 2017 and December 2017. Then VA, Eye movements, cycloplegic refractions and detailed retinal examinations were also examined by this ophthalmologist. Results: Among 462 patients, 239 (51.7%) were male and 223 (48.3%) were female. Various refraction defects were detected in 350 patients (75.8%). We detected myopia in 138 (29.9%) patients, hypermetropia in 102 (22.1%) patients, and astigmatism in 110 (23.8%) patients. Amblyopia was noted in 61 patients (13.2%), and it was caused by anisometropia in 32 patients (6.92%), ametropia in 18 patients (3.89%), pseudophakia in 2 patients (0.43%), corneal opacity in 2 patients (0.43%), and nystagmus in 1 patient (0.22%). Conclusion: Visual impairment is commonly noted in school-age children referred to outpatient clinics by counselors. Thus, more screenings areneeded to provide early and effective diagnosis, treatment, and vision rehabilitation in school-age children.